Pediatric cardiopulmonary resuscitation in infant and children with chronic diseases: A simple approach? - Uzun, Davut D.; Lang, Kristin; Saur, Patrick; Weigand, Markus A.; Schmitt, Felix C. F. (Frontiers in Pediatrics, 2022)
Infants and children with complex chronic diseases have lifelong, life-threatening conditions and for many, early death is an unavoidable outcome of their disease process. But not all chronic diseases in children are fatal when treated well. Cardiopulmonary resuscitation is more common in children with chronic diseases than in healthy children. Resuscitation of infants and children presents significant challenges to physicians and healthcare providers. Primarily, these situations occur only rarely and are therefore not only medically demanding but also associated with emotional stress. In case of resuscitation in infants and children with chronic diseases these challenges become much more complex. The worldwide valid Pediatric Advanced Life Support Guidelines do not give clear recommendations how to deal with periarrest situations in chronically ill infants and children. For relevant life-limiting illnesses, a "do not resuscitate" order should be discussed early, taking into account medical, ethical, and emotional considerations. The decision to terminate resuscitative efforts in cardiopulmonary arrest in infants and children with chronic illnesses such as severe lung disease, heart disease, or even incurable cancer is complex and controversial among physicians and parents. Judging the "outcome" of resuscitation as a "good" outcome becomes complex because for some, life extension itself and for others, quality of life is a goal. Physicians often decide that a healthy child is more likely to have a reversible condition and thereby have a better outcome than a child with multiple comorbidities and chronic health care needs. Major challenges in resuscitation infants and children are that clinicians need to individualize resuscitation strategies in light of each chronic disease, anatomy and physiology. This review aims to highlight terms of resuscitation infants and children with complex chronic diseases, considering resuscitation-related factors, parent-related factors, patient-related factors, and physician-related factors.